Teacher Perception on Reading Material in Blended Learning At Senior High School - Azizah, Trivira; Yulmiati, Yulmiati; Sesmiyanti, Sesmiyanti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The aim of this research is to observe teacher perceptions on reading material using blended learning at SMAN 4 South Solok. This research conducted using descriptive through a qualitative approach. The participant of this study is one of English teacher at SMAN. The sample was selected purposively because the teacher has implemented reading material in blended learning at her class. The data collect through interview with an audio recorder. The results of this research showed that, the perceptions of English teachers at SMAN 4 South Solok 1) Reading materials developed in blended learning to make students master their learning because the material presented is grouped in detail. 2) Reading materials developed in blended learning was very interesting for students. 3) Reading materials developed in blended learning was according to students' ability levels because students learn more about reading. 4) Reading material developed was easy for students to understand because the material presented was not floating and was more specific. 5) Reading material in blended learning made it easier for teacher and students to interact because there are questions and answers when learning took place. 6) In learning offline, there was not enough time for teacher and students to carry out the learning process, but with online students can study at home and do their exercise so as to achieve a good learning process.